2017
DOI: 10.1371/journal.pone.0187973
|View full text |Cite
|
Sign up to set email alerts
|

Profiling analysis of circulating microRNA in peripheral blood of patients with class IV lupus nephritis

Abstract: Renal involvement in Systemic Lupus Erythematous (SLE) patients is one of the leading causes of morbidity and a significant contributor to mortality. It’s estimated that nearly 50% of SLE individuals develop kidney disease in the first year of the diagnosis. Class IV lupus nephritis (LN-IV) is the class of lupus nephritis most common in Colombian patients with SLE. Altered miRNAs expression levels have been reported in human autoimmune diseases including lupus. Variations in the expression pattern of periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 48 publications
0
51
0
1
Order By: Relevance
“…Our miRNA microarray analysis clearly indicated that miR‐6087 expression was statistically significantly decreased in patients with bladder cancer, although the molecular mechanism of the downregulation of miR‐6087 remains unclear. One report showed miR‐6087 detection in patients with class IV lupus nephritis, which is commonly developed in patients with systemic lupus erythematous in the Colombian population . In the paper, Navarro‐Quiroz et al show the upregulation of miR‐6087 in serum samples of patients with lupus nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…Our miRNA microarray analysis clearly indicated that miR‐6087 expression was statistically significantly decreased in patients with bladder cancer, although the molecular mechanism of the downregulation of miR‐6087 remains unclear. One report showed miR‐6087 detection in patients with class IV lupus nephritis, which is commonly developed in patients with systemic lupus erythematous in the Colombian population . In the paper, Navarro‐Quiroz et al show the upregulation of miR‐6087 in serum samples of patients with lupus nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we described for the first time that miR-760, miR-3677-3p, miR-548ah-3p, miR-548p, miR-320e, and miR-23c were up-regulated in the DN patients. Although miR-133a-3p and miR-153-3p have been reported to have implications in pig kidneys [24] and lupus nephritis [25], this is the first time they were reported in the nephrotic DN patients.…”
Section: Urinary-exosomal Mir Signaturesmentioning
confidence: 75%
“…were the top three up-regulated exosomal miRNAs, whereas hsa-miR-6800-3p, hsa-miR-6716-3p, and hsa-let-7i-5p were revealed to be markedly down-regulated. Hsa-miR-6087 has been previously reported to act as an important mediators of cancer [44,45],intermediate monocytes [46]and regulation of cell differentiation [47]. Has-miR-663a is located in the chromosome 20q11.1 and has been reported to be closely related with the biological behavior of cell differentiation, inflammation, autoimmune diseases, and cancer [48][49][50].…”
Section: Discussionmentioning
confidence: 99%